True triaxial experimental study on the influence of axial pressure on coal permeability - Liu, Jianbao; Song, Zhimin; Yang, Chengtao; Li, Bing; Ren, Jiangang; Xiao, Ming (Frontiers in Earth Science, 2022)
The permeability of coal is a key parameter affecting coal and gas outbursts and coal seam gas drainage. The permeability is clearly affected by geo-stress. In this study, the influence of the axial pressure on the permeability of the coal seam was studied using a self-developed true triaxial stress permeability experimental device to set fixed gas and confining pressures, and to change the magnitude of the axial pressure. The experimental results show a polynomial relationship between the axial pressure and the permeability of the coal seam. With an increase in axial pressure, the permeability initially decreased slightly and then increased gradually. When the axial pressure exceeded 30 MPa, the permeability of the coal seam sharply increased. This may be due to plastic deformation of the coal seam under a large axial pressure, resulting in new fractures and significantly improving the permeability of the coal seam. Using the COMSOL numerical simulation software, the effect of in situ stress on the coal seam gas drainage efficiency was calculated by comprehensively considering the adsorption/desorption, diffusion, and seepage of gas. The calculation results show that with an increase in the axial pressure, the gas drainage efficiency of the coal seam increases continuously. As the axial pressure increased from 5 to 30 MPa, the gas drainage efficiency increased to 2–3 times that of the original value.